(untitled) (Alternautas, 2022)
Since the dawn of the 21st century, indigenous identities and knowledge stand at the center of a scenario where new levers for social change are desperately sought for. In that scenario, indigenous knowledge and practices are taking on an increasingly important role in economic and social progress (Briggs ‎2005; Cleaver 1999). However, several authors argue that indigenous experiences and understandings have been idealized, leading to a process of de-politicization (Briggs ‎2005; Cleaver 1999; Zimmerer 2014). Their criticism is not based on the effectiveness of indigenous knowledge, but on its instrumentalization in order to support actions demanding social change (Cleaver 1999). These arguments made by Briggs, Cleaver and Zimmerer inevitably raise questions about the ways in which politics (and academia) produce knowledge about indigenous people and practices that reproduce de-contextualized representations.